Pola Interaksi Sosial Guru Terhadap Murid Kelas XI di SMK Negeri 1 Muara Wahau - Muhammad Yasin; Fira Rusdianti Nasution (Yayasan Literasi Sains Indonesia, 2022)
The existence of a teacher-student interaction model cannot be separated from the world of education. Social interaction is the interaction between two or more human individuals. One person's behavior influences, changes, or enhances the behavior of others. This also applies to the teacher-student relationship in the learning process. The aim of the researcher is to find out how the teacher's interaction with class XI students at SMK Negeri 1 Muara Wahau is and how the principal factors form social interaction. The formulation of this research are: 1). How the Teacher's Interaction with Class XI Students at SMK Negeri 1 Muara Wahau. 2). How are the principal factors for the formation of social interaction? This study uses a qualitative method which aims to describe the interaction pattern of social teachers with students in the classroom. Based on the results of research found in SMK Negeri 1 Muara Wahau, the pattern of teacher-student interaction greatly influences the teaching and learning process in the classroom and the main factors that shape social interaction, there is a relationship that social interaction factors can be influenced by several factors such as imitation, suggestion, sympathy, sympathy, and empathy